Character Management in Crisis: Implementation of Five Day in Ma’had as a Social Care Solution in Elementary Madrasah - Sanjani, Muhammad Aqil Fahmi; Safitri, Sevia Diana; Febrianto, Febi (JUMPA : Jurnal Manajemen Pendidikan, 2024)
This study aims to explore the implementation of the "Five Day in Ma'had" program in Madrasah Ibtidaiyah as a solution to increase social awareness among students. This is very important because good character education management can form students with noble morals and strong characters, which greatly influences their self-development and the overall quality of education. The research method used is qualitative descriptive, with data obtained through interviews, observations, and documentation, and analyzed using data triangulation techniques. The results of the study indicate that the integration of character education in the curriculum can educate students' intellectuality and character at the same time, the role of teachers becomes very crucial as role models, character development programs become more intensive with five days of living in the ma'had, social activities, and community support play a significant role in increasing students' social awareness. This writing is expected to be able to provide practical and theoretical insights into how the "Five Day in Ma'had" program can be implemented effectively in other madrasahs to foster strong and socially aware students' characters.